PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP CASH FLOW SHOCKS - Ayem, Sri; fransiska, imelda (JURNAL RISET AKUNTANSI TIRTAYASA, 2021)
The purpose of this study is to determine the effect of capital structure and profitability on cash flow shocks on manufacturing companies listed of Indonesia Stock Exchange in 2015 – 2019. The data source used in this research is secondary data. The population in this study is manufacturing companies listed in Indonesia Stock Exchange. Data collection methods in this study used purpose sampling. Data analysis technique uses multiple linier regression and classical assumption test. The result showed that capital structure has no significant negative effect on cash flow shocks with a significance level of  0.741> 0.05. profitability has a significant positive effect on cash flow shocks with a significance of  0.001 < 0.05. Keywords : struktur modal, profitabilitas, cash flow shocks